2022
DOI: 10.3390/app122010681
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Compressive Strength, Ultrasonic Characteristic and Cracks Distribution of Granite Rock Irradiated by a Moving Laser Beam

Abstract: Efficient fracturing is the key issue for the exploitation of geothermal energy in a Hot Dry Rock reservoir. By using the laser irradiation cracking method, this study investigates the changes in uniaxial compressive strength, ultrasonic characteristics and crack distributions of granite specimens by applying a laser beam under various irradiation conditions, including different powers, diameters and moving speeds of the laser beam. The results indicate that the uniaxial compressive strength is considerably de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Zhang et al [5] proposed a cluster microseism-based method to improve the prediction accuracy of mining earthquakes. Kuang et al [6] investigated changes in the strength, ultrasonic characteristics, and crack distributions of granite after applying a laser beam under various irradiation conditions. The results indicated that the laser irradiation technique can efficiently identify fracture graphite.…”
Section: Mechanical Properties Of Rocks Under Different Conditionsmentioning
confidence: 99%
“…Zhang et al [5] proposed a cluster microseism-based method to improve the prediction accuracy of mining earthquakes. Kuang et al [6] investigated changes in the strength, ultrasonic characteristics, and crack distributions of granite after applying a laser beam under various irradiation conditions. The results indicated that the laser irradiation technique can efficiently identify fracture graphite.…”
Section: Mechanical Properties Of Rocks Under Different Conditionsmentioning
confidence: 99%
“…Particularly, saturated rocks are more significantly affected. The thermal shock effect of liquid nitrogen can cause shrinkage deformation and reduced pore volume in dry rocks [33,34]. When liquid nitrogen infiltrates the pores and fractures of rocks and forms ice crystals, the expansion of water during the freezing process can generate stress within the rocks, leading to damage and fracture at weakly bonded mineral particle interfaces and potentially causing fractures through propagation.…”
Section: Introductionmentioning
confidence: 99%